2018
DOI: 10.1002/jeab.477
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the repeatability of resurgence in humans: Implications for the use of within‐subject designs

Abstract: Resurgence refers to the recurrence of a previously reinforced response following the worsening of reinforcement conditions (e.g., extinction) for an alternative response. Because of the implications for treatment relapse, researchers have become particularly interested in mitigating resurgence of human behavior. Some studies have employed reversal designs and varied parameters across replications (e.g., ABCADC) to compare effects of second‐phase variables. Although resurgence is generally repeatable within an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Another limitation specific to Experiment 2 worth noting is that all participants had prior exposure to a resurgence procedure in Experiment 1. Other investigators have demonstrated previously that (a) resurgence is a repeatable phenomenon within subjects and (b) the magnitude of resurgence tends to decrease across successive assessments (e.g., Kestner, Diaz‐Salvat, St. Peter, & Peterson, ; Lieving & Lattal, ; Volkert et al, ). Thus, it remains uncertain whether, and if so, to what extent outcomes from this experiment may have been affected by the participants learning history with similar procedures.…”
Section: Discussionmentioning
confidence: 93%
“…Another limitation specific to Experiment 2 worth noting is that all participants had prior exposure to a resurgence procedure in Experiment 1. Other investigators have demonstrated previously that (a) resurgence is a repeatable phenomenon within subjects and (b) the magnitude of resurgence tends to decrease across successive assessments (e.g., Kestner, Diaz‐Salvat, St. Peter, & Peterson, ; Lieving & Lattal, ; Volkert et al, ). Thus, it remains uncertain whether, and if so, to what extent outcomes from this experiment may have been affected by the participants learning history with similar procedures.…”
Section: Discussionmentioning
confidence: 93%
“…In other studies, returning to Phase‐1 training has produced similar or greater resurgence with repeated testing (e.g., da Silva, Maxwell, & Lattal, 2008; Doughty, da Silva, & Lattal, ). In a study with university students, Kestner, Diaz‐Salvat, St. Peter, and Peterson () found a reduction in resurgence with the second exposure to the third of three phases of a resurgence procedure. As a whole, therefore, the existing literature to date is unclear whether repeated testing tends to mitigate return of target responding when there is a return to Phase‐1 training between tests.…”
Section: Resultsmentioning
confidence: 99%
“…This approach minimized one potential source of variation present in other studies of resurgence that used within-subject methods. Specifically, repeatedly presenting the three phases comprising resurgence assessments can reduce resurgence during subsequent tests (e.g., Cleland et al, 2000;Kestner, Diaz-Salvat, St. Peter, & Peterson, 2018). In addition to avoiding any influence from repeated assessments, alternating sessions during testing also reduces the overall number of sessions required to assess both types of resurgence testing when compared to evaluating such tests sequentially across three-phase assessments.…”
Section: Discussionmentioning
confidence: 99%